The Effect of Perceived Service Quality and Ease of Payment on KAI Access User Satisfaction - Aisyah Raihan Faradila; Amalia Zulfa; Zulfa Dwi Muflikhah; Khairani Zikrinawati; Zulfa Fahmy (Experimental Student Experiences, 2024)
This study aims to determine the perception of service quality and ease of ticket payment significantly influence KAI Access user satisfaction. This study uses a quantitative method by spreading the scale using the Google form on KAI Access users on the island of Java. The sampling technique used was purposive sampling of 100 samples with multiple linear regression data processing techniques. Based on the results of the study, it can be concluded that perceptions of service quality and ease of payment have a positive and significant effect on KAI Access user satisfaction. Therefore, companies must pay attention to and improve service quality and ease of payment to increase KAI Access user satisfaction. The significance value of service quality is 0.014 <0.05. This means that service quality has a significant effect on user satisfaction of the KAI Access application. Then, the significance value of ease of payment is 0.000 <0.05. This means that the ease of payment has a significant effect on user satisfaction of the KAI Access application.